The Differences in Neural Response to Faces and Non-Faces in the FFA: Evidence from the Central to Peripheral Visual Field - Guo, Jiayue; Wang, Bin; Ohno, Seiichiro; Kanazawa, Susumu; Wu, Jinglong (Neuroscience and Biomedical Engineering (Discontinued), 2016)
Background: The human brain has different abilities for the discrimination of an object in the visual field, and these abilities robustly decrease as eccentricity increases. The fusiform face area (FFA) in the human brain has been speculated to prefer processing face perception using functional magnetic resonance imaging studies and has been investigated using object stimuli. These studies found activities in the FFA for non-face objects of expertise in the central visual field. However, the neural responses in the fusiform face area from the central to peripheral visual field remain unknown. Objective: Seven healthy subjects from Okayama University participated in this study. Method: In this study, a wide-view presentation system with functional magnetic resonance imaging (fMRI) was used to investigate the neural responses to face and non-face images (animals, houses, and cars) in both the primary visual cortex (V1) and FFA. Results: The FFA regions showed significant neural responses to objects at all eccentricity positions, but these responses decreased as the eccentricity increased. The FFA exhibited significantly positive neural responses to faces and categories of non-faces at all eccentricity positions. In addition, the neural responses to faces were significantly larger than those to non-faces in the FFA. We used RRV1 (ratio relative to V1) to demonstrate the interactions of eccentricity and category on significantly affected neural processing in the FFA. In the FFA, the RRV1s for images of faces were significantly larger than those for images of houses when they were presented at eccentricities of 0°. Conclusion: More interestingly, we found that the face images exhibited larger decreasing trends than the house and car images, which indicated differences in neural responses to faces and non-faces in the fusiform face area from the central to the peripheral visual field. We proposed that the differences in neural responses to faces and non-faces were likely influenced by experience object perception.
Keywords: fusiform face area (FFA)